HUBUNGAN PENGETAHUAN IBU DENGAN TINDAKAN MOBILISASI DINI PASCA SECTIO CAESAREA DI RUMAH SAKIT UMUM HERNA MEDAN - Zulkarnain Nasution; Tiamas sirait (STIKes Santa Elisabeth Medan, 2021)
Abstract Early mobilization is one of the treatments in mothers with sectio caesarea. Early mobilization in post-sectio caesarea mothers is beneficial for: launching lochea production, initiating postpartum infections, accelerating involution, launching gastrointestinal function, improving smooth blood circulation, and speeding up breast milk function., this study aims to analyze